The occurrence of cycling injuries in the Western Province: A descriptive study - E. S. Bakkes; J. A. Hendry; M. S. Uys (AOSIS, 1993)
0n 21 October 1989, a total of 902 randomly selected cyclists were questioned at the finish of the Burger-Sanlam 100km/50km race to determine the prevalence of cycling injuries in the preceding year. Of the total sample 551 cyclists (61 %) reported they had been injury-free during the 12 month period prior to the investigation. The remaining 351 cyclists had sustained a total of 681 injuries during the same period ie approximately 2 injuries per cyclist per year. The most commonly reported injuries were over-use injuries resulting in pain and discomfort in the back and neck regions (41%), with pain in the knee joint being the second most frequently reported injury (29%). This descriptive study has provided valuable base-line information on the types and frequency of injuries sustained by South African cyclists. In particular, the high number of overuse injuries associated with faulty ergonomics has generated hypotheses for further study. An intimate knowledge of the ergonomics related to the sport, as well as attention to educational programmes is also strongly indicated.